Discipline of the School Principal in Shaping Teacher Motivation - Putri, Sari Nusantara; Apriana, Dewi; Nisoh, Anan; Farid, Rahman (Jurnal Pengabdian Masyarakat dan Penelitian Thawalib, 2025)
This study aims to explain and describe the discipline of school principals, its implementation, and its impact on teachers' motivation. The research was conducted qualitatively using a case study approach. Data was collected through interviews, observations, and documentation. Data processing: condensation, data presentation, and conclusion drawing. Data validity: technique triangulation and source triangulation. The research results show that the principal demonstrates excellent performance in motivating teachers, conducting evaluations, serving as a role model, and creating a positive climate. The assessment of handling complaints, classroom supervision, and open communication achieved an average score of 3.87, reflecting good performance, but with room for improvement. Teachers feel that the principal's discipline supports their work, with an average score of 4.0, and they have respect and trust in the principal (score 4.4). However, the score of 3.6 indicates variation in opinions regarding the influence of discipline on teachers' professionalism.